2011
DOI: 10.1097/01.npr.0000398870.16580.86
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on Testicular cancer

Abstract: Testicular cancer, though generally uncommon, is the most common cancer NPs will see in young men. Advances in surgery, radiation, and cisplatin-based chemotherapy, have made testicular cancer a "model" for a curable cancer. Survivors will likely live many years, but will require lifelong follow-up for possible recurrence and long-term treatment sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Testicular cancer (TC) is the most common solid tumor affecting males between 20 and 40 years old and accounting for approximately 1–1.5% of all cancers in men (1, 2). In the last decades, its incidence showed a progressive increase, particularly in some regions of Europe and Northern America (35). It is a real variegate cancer, characterized by several histological patterns, comprising germ-cell tumors and non-germ-cell tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Testicular cancer (TC) is the most common solid tumor affecting males between 20 and 40 years old and accounting for approximately 1–1.5% of all cancers in men (1, 2). In the last decades, its incidence showed a progressive increase, particularly in some regions of Europe and Northern America (35). It is a real variegate cancer, characterized by several histological patterns, comprising germ-cell tumors and non-germ-cell tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering men aged 15–35, it becomes the most common solid malignancy (Siegel et al, 2012; Viatori, 2012). Moreover, many authors demonstrated an increasing secular trend especially in some regions of Europe and North America (Adami et al, 1994; Richiardi et al, 2004; Zoltick, 2011). Many risk factors have been studied as a pre-disposing factor in the development of this cancer, but only for some there is a high level of evidence (Senturia, 1987; Buetow, 1995).…”
Section: Introductionmentioning
confidence: 99%